State formation in China and Taiwan bureaucracy, campaign, and performance - Strauss, Julia C. ca. 20./21. Jh (Cambridge University Press, 2020)
This is an ambitious comparative study of regime consolidation in the 'revolutionary' People's Republic of China and the 'conservative' Republic of China (Taiwan) in the years following the communist victory against the nationalists on the Chinese mainland in 1949. Julia C. Strauss argues that accounting for these two variants of the Chinese state solely in terms of their divergent ideology and institutions fails to recognise their similarities and their relative successes. Both, after all, emerged from a common background of Leninist party organization amid civil war and foreign invasion. However, by the mid-1950s they were on clearly different trajectories of state-building and development. Focusing on Sunan and Taiwan, Strauss considers state personnel, the use of terror and land reform to explore the evolution of these revolutionary and conservative regimes between 1949 and 1954. In so doing, she sheds important new light on twentieth-century political change in East Asia, deepening our understanding of state formation
Title from publisher's bibliographic system (viewed on 11 Oct 2019)
Introduction : modalities of state building and institution building : bureaucracies, campaigns, and performance -- Virtue and talent in making Chinese states : heroes and technocrats in Sunan and Taiwan, 1949-1954 -- Comparative terror in regime consolidation : Sunan and Taiwan, 1949-1954 -- Performing terror : lenience, legality, and the dramaturgy of the consolidating state -- Repertoires of land reform campaigns in Sunan and Taiwan, 1950-1954 -- Theatres of land reform : bureaucracy, campaign, and the show, 1950-1954 -- Conclusion -- Appendix: List of interviewees -- Documentary collections, reports, and Periodicals
Keywords: Geschichte 1949-1954; Political stability / China / Sunan Yuguzu Zizhixian; Political stability / Taiwan; Bureaucracy / China / Sunan Yuguzu Zizhixian; Bureaucracy / Taiwan; Land reform / China / Sunan Yuguzu Zizhixian; Land reform / Taiwan; State building; China / Politics and government / 1949-1976; Sunan Yuguzu Zizhixian (China) / Poltics and government / 20th century; Taiwan / Politics and government / 1945-1975; Jiangsu -- Süd; Taiwan; Gansu